2016
DOI: 10.1177/0265407516650942
|View full text |Cite
|
Sign up to set email alerts
|

The effects of age, gender, and gender role ideology on adolescents’ social perspective-taking ability and tendency in friendships

Abstract: Social perspective taking (SPT; i.e., the social-cognitive process of inferring another person's thoughts and feelings) is commonly thought to be essential for successful social relationships, yet the bulk of past work on the development of SPT does not consider youths' tendency to engage in SPT in the context of their close relationships. The current study of adolescents (ages 12-17, N ¼ 158) helps move the field forward by distinguishing between adolescents' SPT ability (i.e., whether they are developmentall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 52 publications
0
17
0
5
Order By: Relevance
“…Developmental shifts in social factors, stress sensitivity, and the nature of stressors experienced by females and males suggest that gender differences in coping–depressive symptom associations may be greatest during middle to late adolescence and then dissipate into emerging adulthood. Social pressure to conform to culturally prescribed gender roles is heightened during early to middle adolescence as youth enter a phase of identity formation and increased peer salience (Flannery & Smith, 2016). As a result of these socialization processes, adolescent girls may be more likely to engage in emotion-focused strategies, such as rumination or venting emotions, and social support seeking in comparison to adolescent boys.…”
Section: Role Of Gendermentioning
confidence: 99%
See 1 more Smart Citation
“…Developmental shifts in social factors, stress sensitivity, and the nature of stressors experienced by females and males suggest that gender differences in coping–depressive symptom associations may be greatest during middle to late adolescence and then dissipate into emerging adulthood. Social pressure to conform to culturally prescribed gender roles is heightened during early to middle adolescence as youth enter a phase of identity formation and increased peer salience (Flannery & Smith, 2016). As a result of these socialization processes, adolescent girls may be more likely to engage in emotion-focused strategies, such as rumination or venting emotions, and social support seeking in comparison to adolescent boys.…”
Section: Role Of Gendermentioning
confidence: 99%
“…As a secondary objective, gender differences in the age-varying associations between specific coping strategies and depressive symptoms were investigated across adolescence and emerging adulthood. Based on gender differences in socialization processes, emotional reactivity, and stressor types that emerge during adolescence, we hypothesized that the associations between venting emotions, emotional support seeking, and instrumental support seeking and depressive symptoms would be stronger among females relative to males during the adolescent period (Flannery & Smith, 2016; Oldehinkel & Bouma, 2011; Rose & Rudolph, 2006). We also expected that these gender differences would not be observed during the emerging adulthood period due to developmental advances in social functioning, identity development, and acquisition and application of these coping strategies (Haan, 2013; Skinner & Zimmer-Gembeck, 2015).…”
Section: Aims and Hypothesesmentioning
confidence: 99%
“…On the one hand, mentees could have overestimated their social skills due to a lack of self‐insight or social desirability. On the other hand, for boys, social skills might increasingly become less desired with increasing age, and therefore, self‐reports might give an underestimation (Flannery & Smith, ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, inconsistent with studies that showed neurological maturation during adolescence to be linked to increased social skills (Crone & Dahl, ), in the current study younger and not older mentees reported higher social skills. Research showed that for boys, although their interpersonal competence is increasing with age, they tend to engage in less social behavior due to their gender role ideology becoming more stereotypically (Flannery & Smith, ). This might explain the lower scores on social skills for older boys, which refers to either their actual behavior or the way they self‐reported their behavior.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation